Cohort Profile: The Cambridge Study in Delinquent Development (CSDD) - Farrington, David (Journal of developmental and life-course criminology, 2021)
The Cambridge Study in Delinquent Development (CSDD) is a prospective longitudinal study of 411 London males who were first assessed in 1961–1962 at age 8–9. The main aim of the CSDD is to study the development of offending and antisocial behaviour from childhood to adulthood. The males have been interviewed nine times from age 8 to age 48, and they have been searched in criminal records up to age 61. Their parents, children, teachers, peers, and female partners have also been interviewed. Numerous childhood, adolescent, and adult factors have been measured, including individual, family, and socio-economic factors. Up to age 61, 44% of the males were convicted of criminal offences. The CSDD has advanced knowledge about criminal careers, risk factors for offending, the life success and health of offenders, and the effects of life events on the course of development of offending. The CSDD shows how a combination of childhood adversities tends to lead to a combination of adult adversities including offending. Early prevention programmes are needed to interrupt this development and reduce the intergenerational transmission of offending and antisocial behaviour.